Violation of Installing Notary Nameplates Based on the Notary’s Code of Conducts - Fira Adhisa Rivanda (Universitas Negeri Semarang, 2022)
The Notary Code of Ethics aims to be a guideline for Notaries to maintain dignity in carrying out their position as a Notary. Enforcement of the Notary's Code of Ethics must be enforced so that Notaries do not experience irregularities in carrying out their positions, but in practice there are still many who do not pay attention to the provisions as in the code of ethics, especially regarding the arrangement of installing a Notary's nameplate which is regulated in the Notary's Code of ethics tends to be ignored and causes Notaries to experience violations code of Ethics. The purpose of this research is to analyze the arrangements for installing notary nameplates based on the noris code of ethics and efforts to impose sanctions on notaries who violate the code of ethics on installing notary nameplates. This study uses normative juridical by using written legal materials. The results of this study are that the arrangement for installing a Notary's nameplate is regulated in the Notary's code of ethics and Supervision for notaries is carried out by two different institutions, namely the Notary Supervisory Board externally and the Notary Honorary Council internally.